The orientation of colonial churches of fuerteventura - Muratore, Maria Florencia (2020)
We use standard tools of Archaeoastronomy to approach the study of orientations, possibly astronomical, of a group of colonial Christian churches. We present preliminary results of the analysis of the precise spatial orientation of nearly fifty chapels and churches of the Canary Island of Fuerteventura (Spain), most of them built from the period of the Norman conquest in the fifteenth century to the nineteenth century. Although some small chapels belonging to the manorial power of the island and other modern churches do not have a well-defined pattern of orientations, the vast majority of the religious constructions of the island (about 35 of the 48 analyzed) have their axis oriented within the solar range, between the extreme azimuths of the annual movement of the Sun when crossing the local horizon. Unlike what was found in other islands of the archipelago, these results suggest that the religious architecture of Fuerteventura faithfully follows the prescriptions contained in the texts of early Christian writers.